KEDUDUKAN WAKAF ASURANSI JIWA DALAM ISLAM - Jalaluddin Jalaluddin (Jurnal Perspektif Ekonomi Darussalam (Darussalam Journal of Economic Perspec, 2021)
Shari'a something from Allah SWT as the creator is for the benefit of the people, it's just that    humans sometimes have not found it because of the limitations of knowledge and His guidance. An example of the interpretation of Zakat, Infaq, Alms and Waqf (Ziswaf) as socio-economic philanthropy for the distribution of wealth from those who have wealth to those who need it more to reduce economic inequality. Compared to zakat, infaq and alms, they are often combined in terms, but people's attention to waqf is somewhat reduced. In fact, each of them has almost the same function, only for waqf, the principal of the property must be eternal /endowment fund, which is handed over for the general benefit only the benefits are continuous which is commonly called amaljariah However, zakat, infaq and alms tend to be for consumptive needs only (emergency fund). Life insurance waqf is one of the waqf planning methods by making an official/legal will of property ownership by giving the waqf concerned in the event of risk/death with the approval of the heirs. However, they can still enjoy the benefits of the waqf assets as long as the wakif is still alive for the wakif family, the public interest of the insurance policy value at maturity in accordance with the provisions of the money waqf fatwa. Islamic life insurance waqf in Indonesia, namely waqf of the benefits of investment and sharia insurance coverage benefits at the same time, by submitting the policy as a form of waqf contract to Nazhir. In this case, people who have unit-linked life insurance policies from insurance companies that have sharia products after they are made into policies and become securities, the benefits or the sum assured and other benefits will be donated. The purpose of this study is to find out how the position of Islamic life insurance waqf in Islamic law according to the Hanafi School. The research method used is normative-empirical qualitative for the benefit of the maqashid sharia. As for the results of the research in legal action, according to the Hanafi school, it is more flexible because waqf objects (a'in) can move temporarily and permanently, even ownership is still by the waqif. The conclusion is that the ownership of waqf property cannot be separated from the owner, instead they can take and sell it, meaning that the consequence of waqf is only the contribution of benefits. According to the Hanafi school of thought, the way to preserve waqf objects/objects such as money/sharia life insurance is by means of mudharabah or substitution with eternal goods with risk mitigation. Waqf insurance is a prior plan with a promise contract (wa'ad) and is fulfilled after it becomes the property of the participant/waqif, meaning that with movable object waqf such as life insurance, you do not have to wait to be rich before waqf. Moreover, waqf can be temporary (mu'aqqad) or forever (mu'abbad) but the benefits are forever (mu'abbad). Seeing the current world condition that is hit by a crisis, from various literature studies and field research including interviews and observations, the researcher concludes that the view of the Hanafi School of Law is suitable to be applied.Keywords: life insurance waqf law, the Hanafi school of thought, maslahahAbstrakPensyariatan sesuatu dari Allah SWT sebagai sang pencipta adalah untuk kemaslahatan umat, hanya saja manusia terkadang belum menemukan karena keterbatasan ilmu pengetahuan dan hidayah-Nya. Contoh penyariatan Zakat Infak Sedekah dan Wakaf (Ziswaf) sebagai filantropi sosial-ekonomi untuk distribusi kekayaan dari yang mempunyai harta ke lebih membutuhkan untuk mengurangi kesenjangan ekonomi. Dibandingkan zakat infak dan sedekah sering digabung dalam istilah, tapi perhatian masyarakat dengan wakaf agak sedikit berkurang . Padahal sesungguhnya masing-masing mempunyai fungsi yang hampir sama, hanya saja untuk wakaf, pokok dari harta harus kekal/dana abadi (endowment fund), yang diserahkan untuk kemaslahatan umum hanya manfaatnya yang terus menerus yang biasa disebut amal jariah. Tetapi untuk zakat, infak dan sedekah lebih cenderung  untuk kebutuhan konsumtif  saja (emergency fund).  Wakaf asuransi jiwa adalah salah satu metode perencanaan wakaf dengan cara membuat suatu wasiat secara resmi/legal dari kepemilikan harta dengan memberikan wakaf yang bersangkutan disaat terjadi risiko/wafat atas persetujuan ahli waris.  Akan tetapi masih bisa menikmati manfaat dari aset yang diwakafkan tersebut selama wakif tersebut masih hidup untuk keluarga wakif, kepentingan umum dari nilai polis asuransi saat jatuh tempo sesuai dengan mengacu pada ketentuan fatwa wakaf uang. Wakaf asuransi jiwa syariah di Indonesia yaitu mewakafkan hasil manfaat dari investasi dan manfaat pertanggungan asuransi syariah sekaligus, dengan menyerahkan polis sebagai bentuk akad wakaf kepada nazhir. Dalam hal ini masyarakat yang memiliki polis asuransi jiwa unit link dari perusahaan asuransi yang memiliki produk syariah setelah dijadikan polis dan menjadi surat berharga maka manfaatnya atau uang pertanggungannya dan manfaat lainnya itu yang akan diwakafkan. Tujuan dari penelitian ini untuk mengetahui bagaimana kedudukan wakaf asuransi jiwa syariah dalam hukum Islam menurut Mazhab Hanafi. Metode penelitian yang digunakan adalah kualitatif normatif-empirik untuk kemaslahatan dengan patokan maqashid syariah. Adapun hasil dari penelitian secara perbuatan hukum menurut mazhab Hanafi lebih fleksibel karena bisa wakaf benda (a’in) bergerak bisa sementara dan selamanya bahkan kepemilikan masih oleh pewakif. Kesimpulannya bahwa kepemilikan harta wakaf tidak lepas dari pemiliknya, malah dapat mengambil dan menjualnya,  artinya konsekuensi  wakaf hanya kontribusi manfaat saja. Masih menurut Imam Mazhab Hanafi cara pengekalan objek/benda wakaf seperti uang/asuransi jiwa syariah dengan cara mudharabah atau substitusi dengan barang yang kekal dengan mitigasi risiko. Wakaf asuransi adalah perencanaan lebih dahulu dengan akad janji (wa’ad) dan ditunaikan setelah sah menjadi milik peserta/waqif, artinya dengan wakaf benda  bergerak seperti asuransi jiwa tidak menunggu kaya dulu baru wakaf. Apalagi wakaf bisa untuk sementara waktu (mu’aqqad) atau selamanya (mu’abbad) tetapi manfaat untuk selamanya (mu’abbad). Melihat kondisi dunia sekarang yang dilanda krisis, dari bermacam studi literature dan penelitian lapangan (field research) meliputi wawancara dan observasi maka  peneliti menyimpulkan pandangan Imam Mazhab Hanafi cocok diterapkan.